(untitled) (Indian Journal of Public Health Research & Development, 2023)
Objectives: The objective of this study was to estimate the costs and expenses incurred by patients for the management of non-communicable diseases (NCDs). Methods: The study was carried out in 7 Basic Health Centers (BHCs) distributed all over Greater Tunis and was conducted using a new tool: the COPAQ. Results: According to the survey, the direct medical cost was estimated at 127 ± 204.4 TND, while the indirect cost was estimated at 21.58 ± 39.07 TND and the patient spend a total cost of about 149.1 ± 212.2 TND. Compared to the guaranteed interprofessional minimum salary, which is set at 378.560 TND, and to the monthly income of the interviewed patients, which varies between 300-600 TND, the total cost of chronic diseases seemed to be enormous and not affordable for most patients. Conclusions: The Tunisian state should take into consideration the incurred expenses and move towards preventive strategies to decrease the spread of these diseases and thus reduce their costs